2021
DOI: 10.1177/00368504211011878
|View full text |Cite
|
Sign up to set email alerts
|

Social media (Facebook) improper use and the influence of sleeping quality in Taiwan’s university students

Abstract: This study examines the relationship between Facebook (FB) usage and addiction level, and sleep quality of university students. A Google Forms questionnaire was prepared and disseminated via the authors’ FB profile for university students to fill out. A total of 277, including two studying overseas, took part in this research. Among the survey respondents, over 60% ( n = 144) were medical students ( p = 0.000); over 30% ( n = 84) were always logged into FB; the average and daily usage time of most was 5 to 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…These observations were consistent with a Dutch study which found that people went to sleep late due to deliberate procrastination where they felt they deserved time to themselves, mindless procrastination where they were preoccupied with evening activities, and strategic delay where they felt going to sleep later would let them fall asleep faster [82]. Similarly, Wang et al [83] found that, among students at a university in Taiwan with a high use of social media, 61% categorized their sleep quality as poor and may be likely to develop social media addiction and sleep disorders. Additionally, noise pollution and its influence on quality of life and sleep has been increasingly recognized to have detrimental effects on human health, impacting upon general well-being, mental health, diabetes, and obesity [84].…”
Section: Multilevel Factors Influencing Sleepsupporting
confidence: 88%
“…These observations were consistent with a Dutch study which found that people went to sleep late due to deliberate procrastination where they felt they deserved time to themselves, mindless procrastination where they were preoccupied with evening activities, and strategic delay where they felt going to sleep later would let them fall asleep faster [82]. Similarly, Wang et al [83] found that, among students at a university in Taiwan with a high use of social media, 61% categorized their sleep quality as poor and may be likely to develop social media addiction and sleep disorders. Additionally, noise pollution and its influence on quality of life and sleep has been increasingly recognized to have detrimental effects on human health, impacting upon general well-being, mental health, diabetes, and obesity [84].…”
Section: Multilevel Factors Influencing Sleepsupporting
confidence: 88%
“…According to the statistical investigation, there is a connection between personality traits and Facebook addiction. According to McLeod [ 40 ], Eysenck’s personality traits—Extraversion—Introversion, Neuroticism—Stability, and Psychoticism—are characterized in terms of polar opposites. These personality dimensions and their second-order personality traits can also be used to explain the study’s findings.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, persons who exhibit Neuroticism Personality Traits are more likely to develop a Facebook addiction. This may be due to the fact that people with neurotic personality traits frequently experience sudden spikes in anxiety and mood without any warning [ 40 ]. These teenagers may find it challenging to communicate with their peers in person as a result of having neurotic personality traits [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facebook overuse has a negative influence on their academic achievements (Feng et al , 2019). Sleep disturbance of the students is found to be the most harmful of the effect of overuse of this social networking site (Wang et al , 2021). While most of these studies focus on the underlying causes of using Facebook and the effect of over usage, there are few studies relating the possible gender dimension of Facebook behavior.…”
Section: Literature and Predictionsmentioning
confidence: 99%